Environmental Based Activities and Technology Entrepreneurship Growth in North Western Nigeria - Mansur, Muhammad Salahudeen; Abuga, Isaac (NIU Journal of Social Sciences, 2017)
The packages of services offered by an incubator are designed to enhance the success and growth rates of technology startups thus maximizing their impact on economic development. Environmental based activities are those services offered by incubators in collaboration with other government agencies. This paper attempted to empirically assess the contributions of these activities to Technology Entrepreneurship Growth in North Western Nigeria. Positivist epistemology with objective ontology together with interpretive epistemology with subjective ontology was employed. The study used cross-sectional, descriptive and correlational designs, employing quantitative and qualitative approaches.  The data were collected using non standardized instrument, with items on Environmental Based Activities and Technology Entrepreneurship Growth, with a sample size of 86. The instruments were tested for their validity and reliability. The data were analyzed at uni-variate, bi-variate and multivariate levels using frequency, percentages, mean, correlation and regression. The results showed that environmental based activities correlates (57.4%) and contribute to growth at 5% level of significance with p<0.001 and R 2 =0.33 implying that 33% of the variation growth is explained by the variable.  The study found out that physical infrastructural deficit, absence of science parks and lack of synergy amongst the agencies providing these services were the major causes of incubated enterprises failure in North Western Nigeria.  Government should therefore provide the required physical infrastructures itself or through partnership with the private sector.  To decongest incubators and make post-incubation visits easy, science parks should be established. Government agencies providing services to incubatees outside the incubator should synergize efforts in order to make the desired impact. Keywords:   Technology Incubation, Incubators, Incubatees, Science Parks, Technology Entrepreneurship Growth.